Avaliação da expansão de células estromais mesenquimais em biorreator de fibra oca - Santos, Diogo Peres dos (2013)
The use of mesenchymal stromal cells (MSCs) for clinical therapy has been limited by the low amount of cells that can be obtained directly from tissue, making it necessary to develop techniques for in vitro cell number expansion. The current methods of expansion are laborintensive, exhibit unfavorable environments for cell growth, show still modest levels of expansion and low yield in the recovery of these cells. In the search for better alternatives, several types of bioreactors have been assessed, however, with results still discreet. A littlestudied system, which has showed itself very effective in the use with other types of animal cells, is the hollow fiber bioreactor. This bioreactor has relatively homogeneous culture environment, low level of hydrodynamic stress on cells and the process control is made through manipulation external to the culture. Thus, it is proposed in this work the study of the in vitro expansion of MSCs in 15 mL hollow fiber prototype bioreactor designed and built with a configuration specifically conceived for expansion of MSCs for use in therapeutic applications. The inoculum was prepared with MSCs precultured adhered to microcarrier Cultispher-S at concentration of 4 g/L in spinner flask containing 50 mL of α-MEM culture medium with 15% v/v fetal bovine serum. The preculture was performed in CO2 incubator at pH close to 7.3 and temperature of 37°C. For bioreactor expansion cultures, it was used the same culture medium, with addition of 12 g/L of alginate and 4.25-4.50 mM of CaCl2 as gelling agents to immobilize and keep in suspension the microcarriers, in the conditions of pH and temperature used in the preculture. The oxygenation of the culture medium continuously recirculated through the intracapilar space was carried out by air bubbling in an external flask. The oxygenation levels were of 70 to 90% of saturation with air. The experimental results obtained show that the used configuration of hollow fiber bioreactor promoted good conditions for expansion of MSCs without cell aggregation, reaching 15.3-fold expansion and cell recovery levels of 82%. These results also demonstrate the possibility of improving the efficiency of MSCs expansion through the renewal of medium to maintain suitable levels of arginine, nutrient present in limiting amounts, and ammonium, growth inhibitor metabolite.